THE EFFECT OF CODE SWITCHING ON ENGAGING NON-ENGLISH MAJOR STUDENTS - Fransisca Endang Lestariningsih (Sanata Dharma University Yogyakarta, 2019)
When speakers share two or more languages in common, they often switch their languages in a conversation. It is true in the classes where both teachers and students must use a certain language as the language of instructions, as happening in the English classes of Computer Science students in Indonesia. Some teachers tend to always use English all the time with some considerations, whereas others often practice code-switching in the instructional process with other reasons, as well. This study is an observation of the effect of code switching to engage students in two English for computer science classes, in which the teacher in one class used code-switching and the other did not.DOI: doi.org/10.24071/ijiet.2019.030206